Human Capital Education Management and Supply Chain Recovery Strategies in State-Owned Construction Companies: PT Waskita Karya Economic Equilibrium Approach - Buyung W Prinatama (Graduate Program Magister Manajemen Pendidikan, 2026)
PT Waskita Karya (Persero) Tbk (WSKT) faces significant challenges in procurement management, leading to project delays and cost overruns. This study aims to analyze the causes of low vendor participation through the perspective of supply-demand curves and proposes strategic solutions to restore market equilibrium. The methodology employed is a case study with a qualitative descriptive analysis, supported by microeconomic modeling. The results indicate that supply inelasticity, driven by payment risks, causes a leftward shift in the supply curve, creating a deadweight loss. This article recommends five integrative strategies: the establishment of a Vendor Support Center (WISE), Debt-to-Asset Shareholding negotiations, dynamic pricing mechanisms, the use of Memorandums of Understanding (MoU) during the tender phase, and early completion incentives. Moving beyond traditional operational perspectives, the study offers original contributions through the quantification of deadweight loss caused by vendor payment risks and the introduction of the WISE framework to restore supply elasticity. Key innovations include a unique